2017
DOI: 10.14382/epitoanyag-jsbcm.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of aluminium dross as asphalt filler

Abstract: Asphalt industry finds itself battling ongoing economic difficulties and an urge to achieve a more sustainable development and growth. it means constant searching is needed for alternative materials and possibilities to use recycled and processed waste materials in asphalt mixes as long as an expected level of performance and durability is provided. Aluminium dross is a recyclable by-product of the casting process of melted aluminium. in this study an attempt was made to reveal the potentials of using aluminiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Final conclusions about the usage of aluminum dross waste as a passing sieve (No. 200) in asphalt mixes are offered by Soós et al [11] after the qualities of fillers and the results of various mechanical tests are analyzed. It was observed that adding dross in place of the limestone filler stiffens the asphalt mixture and raises the phase angle.…”
Section: Introductionmentioning
confidence: 99%
“…Final conclusions about the usage of aluminum dross waste as a passing sieve (No. 200) in asphalt mixes are offered by Soós et al [11] after the qualities of fillers and the results of various mechanical tests are analyzed. It was observed that adding dross in place of the limestone filler stiffens the asphalt mixture and raises the phase angle.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the composition of alternative and control fillers, milled filler fractions (d < 0.063 mm) were employed for microstructural analyses. Performance-based and performancerelated asphalt mechanical tests using conventional criteria explored how replacing limestone filler with aluminum dross filler affected asphalt mix performance [12]. In another study, laboratory tests of modified asphalt concrete with aluminum and polymer waste composite affect pavement mixtures.…”
Section: Introductionmentioning
confidence: 99%